Playground: just a Place to Go out or a Space for Child Development? - Kotliar I.A.; Sokolova M.V. (Психолого-педагогические исследования, 2019)
The article discusses the relevance of modern play spaces to the tasks of the mental and physical child development, as well as modern approaches to the examination of children's outdoor play environment. A historical analysis of changes in domestic and foreign theories about ideas - what kind of playground children need, also empirical studies of child behavior at different play environment allow us to highlight the main lines of psychological and pedagogical analysis of play spaces. New standards in the field of education and development, as well as in designing educational environment, the request of teachers and designers (architects, engineers) makes relevant to work out the methodological support of the creation of play environment. Interdisciplinary approach and dialogue in this area will allow us to solve the problem of designing such play environment that meets the tasks of the child development.